In situ integration of Fe3N@Co4N@CoFe alloy nanoparticles as efficient and stable electrocatalyst for overall water splitting. (1st November 2021) - Cui, Zihao; Liang, Xizhuang; Wang, Peng; Zhou, Peng; Zhang, Qianqian; Wang, Zeyan; Zheng, Zhaoke; Liu, Yuanyuan; Dai, Ying; Huang, Baibiao
Abstract: Developing highly efficient and stable electrocatalyst for oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) is critical for overall water splitting to solve the shortage of fossil fuel and environment pollution, but it is full of obstacles and challenges. Fe3 N@Co4 N@CoFe alloy nanoparticles were prepared by using an in situ coupling method. The obtained catalyst showed a satisfactory OER performance in alkaline solution with a low overpotential of 225 mV at 10 mA cm −2 current density and a small Tafel slope of 48 mV/dec. Meanwhile, the HER performance was also improved in alkaline solution after cyclic voltammetry (CV) cycles of OER due to the formation of CoFe oxyhydroxides, which required an overpotential of 135 mV to achieve 10 mA cm −2 current density and a Tafel slope of 109 mV/dec. More importantly, the obtained Fe3 N@Co4 N@CoFe alloy electrode and Fe3 N@Co4 N@CoFe alloy-CV electrode (treated through CV cycles of OER) were used as anode and cathode to assemble a two-electrode system for overall water splitting. The constructed system displayed an impressive competency with a voltage of 1.59 V at 10 mA cm −2 current density. The prepared electrocatalysts demonstrated superb long-term stability under 50 mA cm −2 current density for OER, HER and overall water splitting.